Mulher Terena: dos papéis tradicionais para atuação sociopolítica - SenoTêrenoe - kixoku ko´ítukeyea mekuke yoko kóóyene xapa viyénoxapa yoko nâti - Sebastião, Lindomar Lili (2012)
This work program of the Master of Social Sciences, Catholic University of Sao Paulo - PUCSP first contextualizes the Terena people in their historical trajectory from the output of the Paraguayan Chaco. The contact with Brazilian society to the present day, with the focus on the analysis of changes occurring in the cultural sphere of women's roles within their community Terena. Identify which elements were fundamental to this change, pointing to the functions and practices of women and their current social and political field in the village, absorbing new elements from outside, incorporating them into the cultural tradition as a sum. In the mid-nineties start an intensification of women's presence in discussions involving the internal issues. Participation in the sectors covering positions of command, such as associations of women presence in traditional leadership role in school education as teachers, principals of schools in the dual role: the school administration and articulating domestic and foreign policy, presence in universities and search the office of city councilor in the Brazilian national politics, giving a new signification of being a woman Terena